Role of Deagglomeration in Particle Size and Antibiofilm Activity of ZnO Nanoparticles Synthesized with Averrhoa bilimbi Extract - Wonoputri, Vita; Samadhi, Tjokorde Walmiki; Khairunnisa, Shafira; Rahayu, Eka (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Averrhoa bilimbi fruit extract was utilized as a reducing and capping agent in the biosynthesis of zinc oxide nanoparticles, with an emphasis on the effects of in-situ deagglomeration on physical properties and antibiofilm activity against Escherichia coli. The study explored various biosynthesis parameters, namely deagglomeration method (physical vs chemical), temperature (30, 60 ℃), and zinc precursor-to-extract volumetric ratio (0.5 and 2). High purity crystalline ZnO nanoparticles were obtained by calcining biosynthesis precipitates at 375 ℃. The resulting particles consisted of the wurtzite ZnO phase, with diameters ranging from 18 to 30 nm. The hydrodynamic mean particle diameters were 1.0 to 3.5 µm, suggesting the formation of soft agglomerates. Physical deagglomeration was more effective at higher temperatures, while chemical deagglomeration was more efficient at lower temperatures, owing to the interaction between the deagglomeration method and biosynthesis temperature. The biosynthesized ZnO nanoparticles exhibited good antibiofilm activity, achieving a 61% reduction in biofilm population at 50 ppm ZnO, which increased to 78% at a dose of 200 ppm. This activity was improved by lower biosynthesis temperature and precursor:extract ratio, likely due to the preservation of bioactive molecules. The results demonstrate the potential of biosynthesized ZnO nanoparticles as antibiofilm agent, offering enhanced effectiveness compared to commercial ZnO nanoparticles